IMPLEMENTASI FRAMEWORK SCRUM DALAM PENGEMBANGAN DASHBOARD MONITORING UNTUK OPTIMASI PENGELOLAAN DATA INTERFACE - Dwi Diana Wazaumi; Vian Ardiyansyah Saputro; Seftia Khairun Nisa; Sharla Adhita Zahrani (Universitas Budi Luhur, 2025)
In today's digital era, data that is managed efficiently and effectively is a success for a company when facing problems in an ever-changing business. PT XYZ is one of the many companies in the automotive sector, PT XYZ needs to ensure that their interface data can be managed optimally. However, interface data management is often faced with various challenges, such as large volumes of data, continuous monitoring, and the need to identify problems that will arise early. In order to overcome these problems, PT XYZ has a plan to design an application called MyZ as a monitoring solution through a dashboard that aims to monitor files and find potential problems related to interface data. The focus of this study is on the development of the MyZ application as a monitoring dashboard and adopting the Scrum approach to optimize data interface management at PT XYZ. The findings obtained from the development of the MyZ application, this application can show the time needed to send data via email an average of 3.3 seconds, this indicates that the MyZ application allows users to receive information quickly, so that it can speed up the decision-making process. While the presentation of information in the dashboard takes an average of 1.5 seconds. This shows that the MyZ application can provide a fast and efficient response in supporting the interface data monitoring process and minimizing waiting time. This efficiency is very relevant in a dynamic work environment and requires a fast response to data changes.